2008
DOI: 10.1007/s12154-008-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin and mTOR kinase inhibitors

Abstract: Mammalian target of rapamycin (mTOR) is a protein kinase that controls cell growth, proliferation, and survival. mTOR signaling is often upregulated in cancer and there is great interest in developing drugs that target this enzyme. Rapamycin and its analogs bind to a domain separate from the catalytic site to block a subset of mTOR functions. These drugs are extremely selective for mTOR and are already in clinical use for treating cancers, but they could potentially activate an mTOR-dependent survival pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
288
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(294 citation statements)
references
References 86 publications
4
288
1
1
Order By: Relevance
“…In the past 10 years, several agents have been designed to target the mTOR pathway and many other mTOR signaling pathway inhibitors are being studied in clinical trials. Temsirolimus, everolimus, and ridaforolimus are rapalogs that share the same mechanism of action but differ in pharmacokinetic properties because of different substitutions at position C-40 of rapamycin (27,43). The present study found and explained, for the first time, the mechanisms of mTOR participation in the alternative form of tumor blood supply, VM, which provides a novel potential therapeutic target for gliomas.…”
Section: Discussionmentioning
confidence: 57%
“…In the past 10 years, several agents have been designed to target the mTOR pathway and many other mTOR signaling pathway inhibitors are being studied in clinical trials. Temsirolimus, everolimus, and ridaforolimus are rapalogs that share the same mechanism of action but differ in pharmacokinetic properties because of different substitutions at position C-40 of rapamycin (27,43). The present study found and explained, for the first time, the mechanisms of mTOR participation in the alternative form of tumor blood supply, VM, which provides a novel potential therapeutic target for gliomas.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, from an interesting point of view in clinical practice, the interaction of cisplatin with temsirolimus was also reported [26]. The temsirolimus is a rapamycin ester, a machrolid antibiotic used as an immunosuppressor drug in the prevention of transplants rejection [31,32]. This immunosuppressor drug is not cytotoxic by itself, but is able to synergistically increase the cytotoxicity of cisplatin.…”
mentioning
confidence: 99%
“…Probably this is related to the fact that rapalogs are primarily cytostatic, and therefore effective as disease stabilizers rather than for regression, hence the response rate in solid tumors where rapalogs have been used as a single-agent therapy have been modest [49][50][51][52]. Another reason for the limited success is the presence of feedback loop between mTORC1 and AKT in certain tumor cells.…”
Section: Clinical Indications Of M-tor I In Nontransplant Patients Anmentioning
confidence: 99%